1990
DOI: 10.1088/0022-3727/23/5/021
|View full text |Cite
|
Sign up to set email alerts
|

Arrangement of cells in vegetable tissues

Abstract: The authors study the arrangement of cells in undifferentiated vegetable tissues of five different species. The distribution of the number of sides, the average area (an), perimeter (pn) and side length (ln) of n-sided cells are determined as well as the correlation between the number of sides of a cell and of its neighbours. The results show that vegetable cellular nets obey Aboav-Weaire's law. They also discuss Lewis' law and a possible relation between (pn) and n. The analysis of these structures provides a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
43
1
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 25 publications
5
43
1
1
Order By: Relevance
“…In 2D when the Euler's rule holds: (15) and recognizing that n lok does not depend on moments higher than the second, for simplicity we can write σ instead of σ 2 :…”
Section: The Aboav-weaire Lawmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2D when the Euler's rule holds: (15) and recognizing that n lok does not depend on moments higher than the second, for simplicity we can write σ instead of σ 2 :…”
Section: The Aboav-weaire Lawmentioning
confidence: 99%
“…The parameter a versus parameter σ from the literature[2,4,7,[15][16][17][18][19][20][21][22][23][24][25][26].…”
unclassified
“…Although the micro-dynamics we have considered is idealized and chosen for minimalist study, it is interesting to compare our results with those observed in nature. Most undifferentiated biological tissues are space-filling assemblies of cells where the side distribution is centered around n = 6 and the second moment µ 2 takes values between 0.5 and 1.2; for instance, µ 2 = 0.53 in human epidermis [12], 0.6 ≤ µ 2 ≤ 1.1 in vegetable leaves [13], µ 2 = 0.68 in cucumber epithelia and µ 2 = 1.00 in human amnion [1].…”
Section: T > 1 Liquid T < 1 Glass (A)mentioning
confidence: 99%
“…Systems as diverse as soap froths [6][7][8], cellular tissues and other natural tilings [9,10], magnetic grains or polycrystalline structures [11][12][13][14][15], type I superconductors [16], etc., are, in a statistical sense, geometrically similar. Their overall morphology and growth properties are well described by simple spin models with multiple ground states.…”
Section: Introductionmentioning
confidence: 99%